2010
DOI: 10.1097/shk.0b013e3181cc064b
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Elastase Inhibitor Improves Survival of Rats With Clinically Relevant Sepsis

Abstract: Sivelestat sodium hydrate is a selective inhibitor of neutrophil elastase, which is effective in acute lung injury associated with systemic inflammatory response syndrome. However, the effectiveness of sivelestat in sepsis has not been fully examined. In the present study, the effect of sivelestat on severe sepsis in a rat cecal ligation and puncture (CLP) model was investigated. Adult male Sprague-Dawley rats underwent CLP and were randomly divided into two groups: sivelestat-treated group and saline-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…Neutrophils are considered to be central to the pathogenesis of most forms of ALI (Suda et al, 2010). Lung MPO activity is an indicator of neutrophil accumulation.…”
Section: Hydrogen-rich Saline Ameliorated Pulmonary Inflammatory Respmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils are considered to be central to the pathogenesis of most forms of ALI (Suda et al, 2010). Lung MPO activity is an indicator of neutrophil accumulation.…”
Section: Hydrogen-rich Saline Ameliorated Pulmonary Inflammatory Respmentioning
confidence: 99%
“…It is a leading cause of morbidity and mortality in severely ill patients (Raghavendran and Napolitano, 2011a,b;Ware and Matthay, 2000). The major pathological changes of ALI include impaired gas exchange, neutrophil accumulation, increased vascular permeability and parenchyma injury (Wu et al, 2009;Lee and Downey, 2001;Suda et al, 2010). Endotoxin (LPS), derived from the cell wall of gram-negative bacteria, is thought to be the most important pathogen that leads to the development of ALI.…”
Section: Introductionmentioning
confidence: 98%
“…CLP in rodents results in an early hyperdynamic phase what is followed by a hypodynamic phase, similar to human sepsis [8]. We previously reported the efficacy of sivelestat (a synthetic, specific, low molecular weight neutrophil elastase inhibitor, which has been used clinically for the treatment of acute lung injury) in clinically relevant sepsis using this model [9].…”
Section: Introductionmentioning
confidence: 95%
“…In addition, it has been reported that NE induces the release of IL-8 from cells [15]. Furthermore, NE inhibitor has been reported to induce a significant reduction in serum IL-1β in rats with relevant sepsis [16]. IL-1β acts locally to stimulate chemotaxis and activate neutrophils in ALI and also stimulates the production of extracellular matrix by fibroblasts [17].…”
Section: Discussionmentioning
confidence: 99%